Dexmedetomidine for postoperative delirium in surgical patients: a mini-review of mechanisms, clinical evidence, and practical implementation - Li, Xiao-yan; Yang, Jing-yi; Qiu, Yi; Wang, Cai-xia; Wang, Xiao-dong (Frontiers in Pharmacology, 2025)
Postoperative delirium (POD) is a common acute neurocognitive disorder in the perioperative period, significantly increasing the risks of mortality and long-term functional decline. Dexmedetomidine, a highly selective α2-adrenergic receptor agonist, demonstrates potential for POD prevention through multimodal mechanisms, including sympatholytic effects, neuroinflammation attenuation, and physiological sleep preservation. Clinical evidence indicates its efficacy in reducing delirium incidence in cardiac surgery (risk ratio (RR), 0.57) and elderly non-cardiac surgical patients (RR, 0.51), though with notable population heterogeneity and risks of adverse effects such as bradycardia. Current guidelines recommend a dosing range of 0.1–0.7 μg/kg/h, yet monitoring requirements (e.g., electroencephalogram vs. hemodynamics) vary regionally. Future research should focus on precision dosing (e.g., biomarker-guided approaches), next-generation α2-agonists, and optimized multimodal strategies. The clinical application of dexmedetomidine requires careful risk-benefit assessment and integration into individualized perioperative protocols.